Copyright law for librarians and educators : creative strategies and practical solutions - Crews, Kenneth D. (ALA Editions, 2020)
"This newly revised and updated edition by respected copyright authority Crews offers timely insights and succinct guidance for LIS students, librarians, and educators alike"--